A Temperature Sensor Based on Al/p-Si/CuCdO2/Al Diode for Low Temperature Applications - Dere, A.; Tataroglu, A.; Al-Sehemi, Abdullah G.; Eren, Haydar; Soylu, M.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Springer, 2020)
CuCdO2 delafossite oxide film as an interface layer was coated by sol-gel spin coating on p-Si substrate, and thus an Al/p-Si/CuCdO2/Al diode was fabricated. Scanning electron microscopy (SEM) with energy dispersive spectroscopy (EDS) was used to obtain an image of the CuCdO2 oxide film. The temperature-dependent behavior of the diode was studied by current-voltage (I- V) and capacitance/conductance-voltage (C/G-V) measurements over the 100-400 K temperature range. It is observed that the ideality factor (n) decreases and zero-bias barrier height (Ub0) increases with an increase in temperature. This abnormal behavior of n and Ub0 is attributed to barrier inhomogeneities by assuming Gaussian distribution (GD) at the metal-semiconductor interface. For each temperature, the barrier height values obtained from both the conventional I-V and Norde method show good agreement with each other. The I-V-T characteristics have shown the GD, giving a mean barrier height ( similar to U b0) of 1.04 eV and a standard deviation (rs) of 0.12 V. A modified Richardson plot of [ln(I0/T2) similar to q2rs2/2k2 T2 versus q/kT] yields similar to U b0 and A* as 1.06 eV and 31.21 A cm similar to 2 K similar to 2 (indicating an agreement with the theoretical value of 32 A cm similar to 2 K similar to 2), showing the promise of CuCdO2/Si as temperature sensing with a Schottky junction. In addition, C-V and G-V measurements show that the C value decreases and the G value increases as the frequency increases, depending on a continuous distribution of interface states. Also, the capacitance and the conductance values decrease with increasing temperature. The results suggest that Al/p-Si/CuCdO2/Al diode can be used for temperature sensing applications.
Keywords: Schottky diodes; temperature sensing; delafossite oxides; temperature dependence; current; capacitance